2017
DOI: 10.1007/s10072-017-2980-z
|View full text |Cite
|
Sign up to set email alerts
|

The impact on cognitive functions of patients with pituitary adenoma before and after surgery

Abstract: Patients with pituitary adenoma have often suffered cognitive impairment. The study aims to identify the factors, and their impact, that affect the cognitive functions of pituitary adenoma patients. Seventy-six patients with pituitary adenoma were recruited, together with 76 healthy subjects as control. Patients (34 functioning and 42 non-functioning) were randomly assigned into either microscopic (n = 44) or neural endoscopic (n = 32) group. All surgeries were performed through single-nostril transsphenoidal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…However, with physiologically normal levels of the hormone, the postoperative pituitary patients manifested improvement of attention processing, showing similar amplitudes of P200 as the HCs did. Improvement in cognitive functions after surgery was related to the normal endocrine (75). This suggests improvement in attention processing, which could be due to the normalization of hypothalamic-pituitary axes and secretory rhythms of pituitary hormones after removal of the tumor.…”
Section: Discussionmentioning
confidence: 86%
“…However, with physiologically normal levels of the hormone, the postoperative pituitary patients manifested improvement of attention processing, showing similar amplitudes of P200 as the HCs did. Improvement in cognitive functions after surgery was related to the normal endocrine (75). This suggests improvement in attention processing, which could be due to the normalization of hypothalamic-pituitary axes and secretory rhythms of pituitary hormones after removal of the tumor.…”
Section: Discussionmentioning
confidence: 86%
“…(85) Endocrine dysfunction plays an important role in cognitive impairment, and may be reversible after surgical intervention. (86) 1.17 Headache due to genetic vascular disorders 1.17.1. Cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) Various types of migraine headaches have been reported in 20-40% of patients with CADASIL, including migraine with typical aura, which accounts for the majority of cases, migraine without aura, migraine aura without headache, basilar migraine, hemiplegic migraine, acute onset aura without headache, migraine with acute onset aura, migraine with prolonged aura and retinal migraine.…”
Section: Headache Due To Pituitary Apoplexymentioning
confidence: 99%
“…One study found that younger patients had better outcomes than older patients after pituitary surgery, 22 while others have not reported a difference. 8,9,24,26,27,34,35 Another study found that presurgery tumor size is negatively correlated with postsurgery outcome, 28 whereas other studies have not. 16,35 Finally, Tooze 33 found a sex difference, with men performing significantly worse than women on tests of immediate memory across a cohort of patients treated for NFA, regardless of treatment group.…”
mentioning
confidence: 99%
“…8,9,24,26,27,34,35 Another study found that presurgery tumor size is negatively correlated with postsurgery outcome, 28 whereas other studies have not. 16,35 Finally, Tooze 33 found a sex difference, with men performing significantly worse than women on tests of immediate memory across a cohort of patients treated for NFA, regardless of treatment group. Interestingly, a previous study 14 added patient sex as a covariate in its analyses, suggesting a difference between men and women in their sample, although this was not independently reported.…”
mentioning
confidence: 99%
See 1 more Smart Citation